EFFECT OF WATER-CEMENT RATIO ON RHEOLOGICAL PROPERTIES OF FOAM CONCRETE MADE OF LOCAL RAW MATERIALS - Kamil A. Otsokov (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Abstract. Objectives  The purpose of this work is to study the dependency of the fluidity of foam concrete mixtures on the water-cement ratio when using various local aggregates and wastes from the Republic of Dagestan and comparing the fluidity characteristics of mixtures for the same watercement ratios. During the experimental work, the following materials were used: M500 cement, siliceous filler (quartz sand from the deposit in the Kumtorkalinsky district of the Republic of Dagestan with a low modulus of grain size, various synthetic foaming agents), perlite sand, ground expanded clay sand (Kizilyurt, Republic of Dagestan), stone crushing screenings (Kizilyurt, Republic of Dagestan). Methods  During the production of foam concrete, a method was used in which foam was prepared in the foam generator, then a solution was prepared from the cement, siliceous component (filler), and water. Then the foam was mixed with the solution in the foam concrete mixer up to the set of the appropriate multiplicity. (The multiplicity in this case was defined as ratio of the volume of the solution of the foam concrete mixture after mixing to the volume of the solution before mixing. During the studies, the water-cement mixture ratio for all three kinds of filler (expanded clay sand, quartz sand from the deposit of the Kumtorkalinsky region, and perlite) was determined. The fluidity index of the foam concrete mixture was determined using a Suttard's viscometer. Results  The results of the research indicated that with an increase in the water-cement ratio for all three types of filler (expanded clay sand, quartz sand from the Kumtorkalinsky region and perlite), the foam concrete mixture fluidity index will increase. Conclusion  With the same fluidity index values, the mixture with perlite filler has the lowest fluidity, which in turn affects the further structure formation of the foam concrete, allowing the optimal composition with the specified properties to be selected.